2015
DOI: 10.1007/s10973-015-4979-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal crystallization kinetics of Zr52Cu18Ni14Al10Ti6 metallic glass

Abstract: In the present work, the thermal analysis of the bulk metallic glass with composition Zr 52 Cu 18 Ni 14 Al 10 Ti 6 has been done by differential scanning calorimetry (DSC) through non-isothermal method. DSC curves indicate a twostep crystallization process at all four heating rates, i.e., 5, 10, 15, and 20°C min -1 . Non-isothermal crystallization studies of the alloy indicate that kinetics conform to Johnson-MehlAvrami (JMA) model. The master plot method and normalized heat flow curve prove the validity of JM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The E a is usually determined with Kissinger method ( Ref 7,8,20,23). It was revealed that the straight line obtained for the E a evaluation refers not only to the high heating rates but also to heating rates from 10 to 140 K/min.…”
Section: Discussionmentioning
confidence: 99%
“…The E a is usually determined with Kissinger method ( Ref 7,8,20,23). It was revealed that the straight line obtained for the E a evaluation refers not only to the high heating rates but also to heating rates from 10 to 140 K/min.…”
Section: Discussionmentioning
confidence: 99%
“…nucleation rate for the crystalline volume fraction between 0.2 and 0.9. Although studies on the crystallization kinetics have been carried out for a series of metallic glasses [7][8][9][10][11][12][13][14][15], data are still in deficiency on the crystallization kinetics of Fe-based metallic glasses.…”
Section: Glassy Alloysmentioning
confidence: 99%
“…Traditionally, studies of the crystallization kinetics were performed on DSC equipment under non-isothermal crystallization and isothermal crystallization conditions. In previous studies, the effective activation energy, crystallized volume fraction, and transition kinetics have been analysed in detail [7][8][9][10][11][12][13][14][15]. Wang et al [7] investigated the crystallization kinetics in the Fe 80 P 13 C 7 alloys and proposed that the crystalline mechanism belongs to the diffusion-controlled growth of the glassy ribbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation